Effects of different forms of barberry root (Berberis vulgaris) on growth performance, muscle fatty acids profile, whole‐body composition, and digestive enzymes of rainbow trout (Oncorhynchus mykiss) - Ramezanzadeh, Sara; Abedian Kenari, Abdolmohammad; Esmaeili, Moha; Rombenso, Artur (Journal of the World Aquaculture Society, 2021)
The supplementation of fish diets with herbal medicines aimed at improving growth and flesh quality is an attractive subject in fish nutrition research. In the present study, the effects of barberry root on the growth performance, muscle fatty acids profile, whole‐body composition, and digestive enzymes of rainbow trout were investigated. A total of 306 rainbow trout fingerlings (15.55 ± 0.76 g) were fed various diets in groups including the control (C), BRP10 (10 g/kg of barberry root powder), BRP20 (20 g/kg of barberry root powder), BRE250 (250 mg/kg of barberry root extract), BRE500 (500 mg/kg of barberry root extract), and OTC30 (30 g/kg oxytetracycline) groups. After 56 days, the results indicated that fish fed the BRE250, BRE500, and OTC30 diets had significantly higher weight gain (592.23, 580.43, and 605.21%, respectively) compared with the other dietary treatments (p < .05). Whole‐body protein and fat content showed significant differences among fish fed the treatments and the control, displaying significantly higher and lower values, respectively, compared with those fed the BRP20, BRE250, and BRE500 diets (p < .05). Muscle in fish fed the OTC30 diet displayed a significantly lower content of omega 3 compared with those fed the BRP20 and BRE500 diets (p < .05). Although digestive enzymes revealed no special trend across dietary groups, fish fed the BRP20 diet presented the highest values of amylase (22 U/mg protein−1), trypsin (57.16 U/mg protein−1), and lipase (5.62 U/mg protein−1). Based on the current findings, barberry root is suggested to be a promising and strategic feed additive in the aquaculture industry as it promotes growth performance and improves flesh quality.